A COVID-19 superspreading event involving two variants during sociotherapy activities in a French mental health centre. (September 2022) - Ferriot, C.; Durance, C.; Trutt, L.; Rozo, C.; Louvigné, C.; Bressollette-Bodin, C.; Birgand, G.
Summary: Background/Purpose: Investigation of a COVID-19 super-spreading event involving both beta and delta variants of SARS-CoV-2, following a choir in a mental health centre. Methods: An epidemiological and biological (RT-PCR, mutations screening and sequencing) investigation was carried out to identify the chains of transmission. A morbidity and mortality review was performed using ALARM root causes analysis to understand how this superspreading event could have taken place. Results: On May 25 and 26, 2021, all 13 choir participants were screened. Of these, eight were positive. None of them was vaccinated. Biological results suggested seven cases of delta variants (three confirmed by sequencing) and one case of beta variant. The screening of 141 contact individuals identified 21 subsequent cases with a suspected delta variant and two cases of suspected beta variant. Since the two index cases had similar Ct during the choir, this suggests different spreading abilities. The contributing factors were multiple, including underestimation of infectious risks by the social therapy team in relation to low individual and collective perceived vulnerability Conclusion: HCPs involved in sociotherapy must be aware of, and trained to mitigate, the risk of superspreading event. Conventional distancing and good natural ventilation appear to not be enough to prevent spread of more transmissible variants of SARS-CoV-2.